HOW IMPORTANT IS ENGLISH LANGUAGE TEACHING IN VOCATIONAL SCHOOLS? - Abdurahmonova Mardona; Begalieva Maftuna (PEDAGOGS, 2024)
Abstract: Teaching English in vocational schools is important for students' comprehensive development and future success. Proficiency in English increases employability, provides access to global resources, facilitates further education opportunities, develops effective communication skills and promotes cultural understanding and diversity. By prioritizing English-language education, vocational schools empower students to succeed in a competitive and interconnected world, providing ample opportunities for personal and professional growth.